Contingency Theory or Universal Theory on Public Organisation? - Achmad Nurmandi (Korea University, 2012)
In this speech I would like to bring up a few matters related to the public organisation. Public organizations have a central role to achieve the greater benefit of mankind, without good organization will not be realized. Therefore ICONPO is one of the important orum for research publication and inform best practices around the world.